2022
DOI: 10.1021/acsorginorgau.1c00035
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Hydrosilylation of Alkynes

Abstract: Herein, the electrochemical hydrosilylation of alkynes is reported. In the presence of the Suginome reagent (PhMe 2 Si− Bpin), a large panel of terminal alkynes and internal alkynes was successfully converted into the hydrosilylated product in good to excellent yields and good selectivity in favor of the linear product. Preliminary mechanistic study supported the involvement of a silyl radical, which reacted on the alkyne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Recent studies show a possible hydrosilylation of alkynes via the electrochemical reaction pathway. [167] However, the oxidation of SiÀ B bonds is beyond the scope of our review and has been already discussed elsewhere. [35] Recent studies by He and co-workers, [69] have shown that the use of a HAT mediator generates a silyl radical that can be scavenged by unsaturated hydrocarbons.…”
Section: Si-c Bond Formationmentioning
confidence: 99%
“…Recent studies show a possible hydrosilylation of alkynes via the electrochemical reaction pathway. [167] However, the oxidation of SiÀ B bonds is beyond the scope of our review and has been already discussed elsewhere. [35] Recent studies by He and co-workers, [69] have shown that the use of a HAT mediator generates a silyl radical that can be scavenged by unsaturated hydrocarbons.…”
Section: Si-c Bond Formationmentioning
confidence: 99%
“…[84][85][86][87][88] Another solution is to use Si-B reagents, which could generate silyl radicals by direct anodic oxidation in the presence of a base (Scheme 21, right, path 2). 89 On the basis of the two strategies, several reports have emerged in recent years to exploit the application of silyl radical intermediates, which expand the potential value of this methodology.…”
Section: Electro-enabled Radical Silylationmentioning
confidence: 99%
“…In 2022, Poisson and co-workers reported an electrochemical hydrosilylation of alkynes without the assistance of NHPI (Scheme 31). 89 In this process, the Suginome reagent (PhMe 2 Si-Bpin) was used to enable the formation of a silyl radical. A large panel of aryl alkynes and alkyl-substituted alkynes could deliver the desired products in good yields with high selectivities in favor of the linear products.…”
Section: Electro-generated Silyl Radicals By Anodic Oxidationmentioning
confidence: 99%
“…In sharp contrast, synthesis of geminal or vicinal borosilanes via radical approaches is rarely explored 19 21 . Even though hydrosilylation of alkenes through hydrogen atom transfer catalysis or single electron transfer catalysis have been developed 19 , 22 28 and many alkenyl boronates are commercially available, regiocontrol in radical hydrosilylation of substituted alkenyl boronates remains challenging (Fig. 1A ).…”
Section: Introductionmentioning
confidence: 99%